The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/su13042061
|View full text |Cite
|
Sign up to set email alerts
|

Up-To-Date Challenges for the Conservation, Rehabilitation and Energy Retrofitting of Higher Education Cultural Heritage Buildings

Abstract: In higher-education world heritage sites, the conservation and energy retrofitting of heritage buildings (HBs) is an important vector for their development, competitiveness and welfare. To guarantee their ongoing use, these buildings must be adapted to face current and emerging societal challenges: (i) the conservation of cultural heritage and the maintenance of their original characteristics and identity; (ii) the transformation of heritage sites into tourist centers that energize the local economy, generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
(39 reference statements)
2
8
0
Order By: Relevance
“…The present finding was also in line with the findings of Irandu and Shah [82] that portrayed the cultural heritage conservation of Kenya faced challenges such as funding, poor enactment of policies, land grabbing and lack of adequate trained personnel. Besides, another finding revealed that tackling the calamities of climate change mainly global warming and extreme weather events combined with the implementation of varied strategies to moderate the impact of a growing tourist demand towards heritage sites become the growing problem in the conservation efforts of cultural heritage conservation which supports the present finding [83]. This finding also revealed the land use issue is an emerging problem for conservation.…”
Section: Regression Resultssupporting
confidence: 85%
“…The present finding was also in line with the findings of Irandu and Shah [82] that portrayed the cultural heritage conservation of Kenya faced challenges such as funding, poor enactment of policies, land grabbing and lack of adequate trained personnel. Besides, another finding revealed that tackling the calamities of climate change mainly global warming and extreme weather events combined with the implementation of varied strategies to moderate the impact of a growing tourist demand towards heritage sites become the growing problem in the conservation efforts of cultural heritage conservation which supports the present finding [83]. This finding also revealed the land use issue is an emerging problem for conservation.…”
Section: Regression Resultssupporting
confidence: 85%
“…Furthermore, heritage value conservation is a specific point of EIQ when considering the preventive conservation approach. This has been taken into account for cultural heritage buildings like museums or higher education [39][40][41].…”
Section: Energy Efficiency Thermal Comfort and Interior Environmental Comfortmentioning
confidence: 99%
“…Walls may present high initial moisture levels and various types of damage, which should be critically evaluated and eventually resolved to avoid post-intervention problems [32]. When dealing with historic constructions, detailed information on the thermophysical properties of the envelope may also be needed [33], and specific in situ measurements should be then performed, such as the evaluation of the U-value of the original walls by means of heat flow meters [34,35]. Additionally, thermography can be adopted as a non-destructive measurement method to identify local heat losses due to defects in the construction (e.g., thermal bridges, air leaks, or gaps in the construction) [32].…”
Section: Thermal Insulation Solutions For Historic Walls: An Open Questionmentioning
confidence: 99%